Curcumin and Cancer: Recent Developments - Shyamasree Ghosh; Sanjima Pal; Smita Prusty; Girish KVS (Journal of Research in Biology, 2012)
Cancer is a malignant disease with high mortality rates affecting millions. Although chemotherapeutic agents are employed largely in cancer management, they often result in toxicity and side effects and may lead to resistance. These draw backs of the conventional chemotherapeutic agents have lead to the urging need for development of safer, biocompatible, nontoxic compounds from natural sources and their application in cancer management. Products from natural sources are being exploited in cancer research worldwide due to its less toxicity. Of the several natural products tested, curcumin, well known for its chemopreventive, cytoprotective and immune suppressive properties holds great promise for cancer research. Curcumin has been reported to affect different signaling pathways either in a direct or indirect manner in a wide range of cancers. Despite the therapeutic effectiveness of curcumin, its application is largely restricted due to its poor absorption, lipophilic nature and low bioavailability. Thus newer and effective formulations for curcumin in cancer treatment are being continuously exploited. In this review we highlighted (i) recent developments of application of natural products in cancer research (ii) role of curcumin in different cancers (iii) curcumin formulations and their application in cancer research. The future scope of this review lies in the effective employment of curcumin and its formulations, in the eradication of cancer.